Role of a Teacher in Innovative Education and Development of Institute - Shankar, Girija (IJRDO-Journal of Applied Science, 2015)
Innovation is defined as “the process of making changes to something established byintroducing something new.” Over the years there have been many changes in the wayeducation is designed and delivered in parts of the world. How can innovation andtechnology offset the barriers of access and mobility that has been a deterrent to education inmany parts of the developing world?